REPRODUCTIVE GROWTH RESPONSE OF SWEET PEPPER (Capsicum annum L) IN SOIL AMENDED WITH FALSE YAM (Icacina oliviformis) TUBER BIOCHAR - Asante, J. K.; Quainoo, A. K. (UDS International Journal of Development, 2022)
Biochar, carbon rich stable solid material, is used mostly for soil amendment. The main objective of this study was to assess false yam tuber biochar performance or effect on the vegetative growth of pepper. Pepper seeds were obtained at Wumpini agrochemical shop in Tamale which were sown, and growth parameters were assessed (germination percentage, plant height, number of leaves and leaf area index). The soil was amended with biochar produced from false yam tuber. The experiment consisted of seven treatments (T1, T2, T3, T4, T5, T6, T0) replicated three times including the control (soil only). The soil and biochar mixture were done in two different levels (6 g/pot and 12 g/pot) each at three different times (four weeks before planting (4WBP), two weeks before planting (2WBP) and at planting (DOP)) with control as soil only. Results obtained indicated that there were no significant differences in germination percentage among the treatments both at one week and two weeks after planting. The highest growth performance (plant height, number of leaves and leaf area index) was recorded in the control. The least growth performance was recorded in treatment T1 (6 g of biochar applied at 4 weeks before planting (4WBP)). The application rate of false yam tuber biochar (6 g/pot and 12 g/pot) as soil amendment might not be the right amendment for sweet pepper production.